1999
DOI: 10.1007/s004280050447
|View full text |Cite
|
Sign up to set email alerts
|

Mixed ductal-endocrine carcinoma of the pancreas presenting as gastrinoma with Zollinger-Ellison syndrome: an autopsy case with a 24-year survival period

Abstract: We report an autopsy case of mixed ductal-endocrine carcinoma of the pancreas presenting as gastrinoma with Zollinger-Ellison syndrome. A 38-year-old Japanese male was found to have Zollinger-Ellison syndrome and pancreatic gastrinoma, and gastrectomy and resection of the pancreatic tumor were performed. However, hypergastrinemia persisted, and the patient died of disseminated carcinomatosis at 62 years of age, 24 years after the onset of Zollinger-Ellison syndrome. At autopsy, the main tumor was present in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 21 publications
(32 reference statements)
2
38
0
Order By: Relevance
“…A resected specimen was used for the diagnosis of mixed ductal-endocrine carcinoma of the pancreas. Seventeen case reports of pancreatic mixed ductalendocrine tumor have been published in English language journals, [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] as shown in Table 1. A literature review with a case report by Iwamuro M et al showed 34 mixed-tumor cases in Japanese reports.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A resected specimen was used for the diagnosis of mixed ductal-endocrine carcinoma of the pancreas. Seventeen case reports of pancreatic mixed ductalendocrine tumor have been published in English language journals, [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] as shown in Table 1. A literature review with a case report by Iwamuro M et al showed 34 mixed-tumor cases in Japanese reports.…”
Section: Discussionmentioning
confidence: 99%
“…During the follow-up period, the case was complicated by gallbladder mucosal adenocarcinoma. 14 Chatelain et al reported mixed ductal-endocrine carcinoma complicated by squamous cell carcinoma of the gingiva. 16 Carter et al reported mixed ductalendocrine carcinoma complicated by papillary carcinoma in situ of the common bile duct.…”
Section: Discussionmentioning
confidence: 99%
“…MANEC is more common in women, although the number of reported cases is small [4][5][6]. Most patients present with abdominal pain and weight loss [3,7,8]. A standardized management protocol has not been established owing to the small number of cases, but complete or debulking surgical resection is generally considered the first line treatment, after which additional chemotherapeutic agents can be applied [3].…”
Section: Discussionmentioning
confidence: 99%
“…As for conventional pancreatic carcinomas, the majority of mixed ductal-endocrine carcinomas occur in the head of the pancreas [37,49], while acinarendocrine carcinomas are equally divided between the head and tail [36,50]. Endocrine-related symptoms may be present, and a case with hypergastrinemia has been reported [69].…”
Section: Meec In the Pancreas Gastrointestinal And Biliary Tractmentioning
confidence: 99%